AI-Based Chatbot Application as Learning Media on Writing Text Description Material - Nurjanah, Elen; Ulfiyani, Rizqiyah (Proceeding International Conference on Education, 2023)
AI technology in chatbot applications can be utilized as a medium learning. Media chatbots can reply to messages automatically with use keywords according to the information needed. In addition, the media it can be accessed anywhere, and anytime. Learning to write description texts you can take advantage of this chatbot application to provide convenience to students in searching for information about objects to be described such as objects schools, tourist attractions, or historical sites. This research aims to describe (1) application of chatbot application as a learning medium to write description text and (2) the benefits of chatbot applications as learning media. This study used a qualitative descriptive approach. Instruments in this research is a lesson implementation plan. Results of this study is an exposure to the advantages of chatbot applications as learning media and implementation.